Identifying the cellular targets of natural products using T7 phage display. Issue 5 (11th March 2016) - Piggott, Andrew M.; Karuso, Peter
Abstract : A description of the T7 phage biopanning procedure is provided with tips and advice suitable for setup in a chemistry laboratory. Abstract : Covering: up to the end of 2015 While Nature continues to deliver a myriad of potent and structurally diverse biologically active small molecules, the cellular targets and modes of action of these natural products are rarely identified, significantly hindering their development as new chemotherapeutic agents. This article provides an introductory tutorial on the use of T7 phage display as a tool to rapidly identify the cellular targets of natural products and is aimed specifically at natural products chemists who may have only limited experience in molecular biology. A brief overview of T7 phage display is provided, including its strengths, weaknesses, and the type of problems that can and cannot be tackled with this technology. Affinity probe construction is reviewed, including linker design and natural product derivatisation strategies. A detailed description of the T7 phage biopanning procedure is provided, with valuable tips for optimising each step in the process, as well as advice for identifying and avoiding the most commonly encountered challenges and pitfalls along the way. Finally, a brief discussion is provided on techniques for validating the cellular targets identified using T7 phage display.